Minimal Hepatic Encephalopathy is an under Recognized Entity in Clinical Practice of Bangladeshi Physician - Abedin, Md Forhad; Abedin, Md Joynal; Mahtab, Mamun Al; Ahmad, Nooruddin (Journal of Bangladesh College of Physicians and Surgeons, 2018)
Background: Minimal Hepatic Encephalopathy, the mildest from of Hepatic Encephalopathy is characterized by subtle motor and cognitive deficits and impairs health related quality of life. Though the prevalence of Minimal Hepatic Encephalopathy in cirrhotic patient is high but awareness regarding MHE is yet not satisfactory. Moreover diagnosis of MHE, the cut off normative value for psychometric test is yet not established in Bangladesh. This is the first study in Bangladesh to find out the normative value for psychometric test and see the prevalence of Minimal Hepatic Encephalopathy in cirrhotic patient. Methods: Cross sectional study done in Department of Hepatology, BSMMU, Dhaka from July 2012 to June 2014. Total 150 patient of which 50 patient with cirrhosis and remaining 100 healthy individual were included in the study. By doing number connection test, Serial dotting test and line tracing test in healthy individual, first normative values for psychometric test was detected then these test was done on cirrhotic patient, whose 2 psychometric test result among 3 above normal value were enrolled as a case of Minimal Hepatic Encephalopathy. None of the patient previously diagnosed as any type of Hepatic Encephalopathy. Results: Cut off normative value for NCT, SDT, LTT is 52 seconds, 52 seconds and 84 seconds respectively (Mean+2SD). Prevalence of Minimal Hepatic Encephalopathy in this study was 66% and it is more prevalent in advanced cirrhosis. Conclusion: MHE is frequent in patient with liver cirrhosis, manifested even in patient with child pugh A liver cirrhosis. Every attention should be given to detect Minimal Hepatic Encephalopathy in patient with cirrhosis of liver well before the development of overt Hepatic Encephalopathy. J Bangladesh Coll Phys Surg 2018; 36(2): 59-63